2015
DOI: 10.1055/s-0034-1392976
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of and risk factors for the surgical resection of nonmalignant colorectal polyps: a population-based study

Abstract: In this population-based study, 4.1 % of patients with nonmalignant polyps were referred for surgical resection. The endoscopist was one important factor that was associated with surgical referral. To further decrease the proportion of inappropriate surgery in patients, endoscopists should refer their patients with large or difficult polyps to expert endoscopists prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 30 publications
5
33
2
Order By: Relevance
“…Referral to surgery for benign polyps >20 mm in size is dependent on the endoscopist and can vary from 0 to 46.6 % per endoscopist. 20 More than 75% of patients with complex colon polyps referred to our EMR center have undergone successful endoscopic resection of their polyps and thereby avoided surgery; about 24% referred to our center have had to undergo primary surgery. Luigiano et al reported similar outcomes, further substantiating the need for referral to an EMR center to avoid unnecessary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Referral to surgery for benign polyps >20 mm in size is dependent on the endoscopist and can vary from 0 to 46.6 % per endoscopist. 20 More than 75% of patients with complex colon polyps referred to our EMR center have undergone successful endoscopic resection of their polyps and thereby avoided surgery; about 24% referred to our center have had to undergo primary surgery. Luigiano et al reported similar outcomes, further substantiating the need for referral to an EMR center to avoid unnecessary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a population‐based study which reported a surgical resection rate of 21% for benign polyps ≥ 20 mm in size highlighted that the diagnosing endoscopist was an important factor in the variation in surgical referral rates. This is consistent with the finding that the specialty of the endoscopist is strongly associated with the accuracy of polyp characterization and treatment recommendations .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are very few reports on outcomes of lesions at the extremes of the spectrum of ER, such as those with extensive or complete circumferential involvement which in the past were routinely referred for surgery. Defining these outcomes is all the more important given that, even in the current era of advanced ER, patients with large colorectal lesions without invasive cancer are still subjected to radical surgery [7,15]. Almost all reports on outcomes of ER resulting in near or total circumferential defects and the risk of stenosis originate from Japanese expert centres focusing solely on ESD, some focusing exclusively on rectal tumours [3][4][5].…”
Section: Discussionmentioning
confidence: 99%